Gender schemas in perception of gender-neutral images - Ekaterina Zizevskaia; Mariia Shchukina (Psychology in Russia: State of Art, 2018)
Background: Gender stereotypes are still a social problem. They display themselves in the process of perception by activating a gender schema as well as androcentrism and gender polarization lenses. Objective: This paper addresses the dependence of perception on social stereotypes and schemas. The research aimed at understanding how a gender-neutral image of a cat is perceived, and checking such factors as gender schema, gender stereotyped context, the animal’s weight, the identification of participants with an animal on basis of their own gender. Design: A Female Cat or Male Cat Test, consisting of 12 pictures, was constructed for this research. We also used the Masculinity, Femininity and Gender Type of Personality Inventory, the Russian version of the Male Attitude Norms Inventory. Tests were conducted on 197 students in Saint-Petersburg and Moscow. Results: A cat was perceived as male 6.4 times more often than as a female, when each case of perception was counted. It was seen as male 7.2 times more often than as a female when we analyzed how the cat was seen in general by each participant. A gender-stereotyped context influenced perception for some participants. There was no influence of the animal’s weight or identification of participants with an animal on basis of their own gender. Conclusions: The research supports the hypotheses that perception of a picture of a gender-neutral animal can be explained mainly by gender schema and the interplay between “lenses” of gender polarization and androcentrism. When the last one was activated, the cat was seen as male. Most of cases when the animal was seen as a female can be explained by the influence of polarization lenses (through gender-stereotyped context in the pictures).